Low energy availability (LEA) in male athletes: A review of the literature - Lee, B. L. (The Sport Journal, 2024)
Purpose Low energy availability (LEA) is a physiological state when there is inadequate energy to meet the demands placed on the body, often through physical activity, exercise, or sports. LEA can impact any athlete engaged in a sport with low energy intake or excessive energy expenditure. LEA is a precursor to the onset of The Male Athlete Triad (MAT) and Relative Energy Deficiency in Sport (RED-S). There is no defined low energy availability threshold specific to male athletes engaged in high-energy expenditure sports leading to MAT and RED-S. This literature review evaluates the literature on the relationship between LEA and signs or symptoms of MAT and RED-S to establish a low energy availability threshold specific to male athletes engaged in high-energy expenditure sports.